2014
DOI: 10.1177/1756283x14530781
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver function decompensation in a patient with sickle cell disease managed with exchange transfusion and endoscopic retrograde cholangiography

Abstract: Sickle cell intrahepatic cholestasis is a relatively uncommon complication of homozygous sickle cell anemia , which may lead to acute hepatic failure and death. Treatment is mainly supportive, but exchange transfusion is used as salvage therapy in life threatening situations. We describe a case of a 16-year-old female with homozygous sickle cell anemia who presented to the emergency room with fatigue, malaise, dark urine, lower back pain, scleral icterus and jaundice. She was found to have marked hyperbilirubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…They were young adults. The literature review from 2001 to 2020 has shown that the incidence is higher in the pediatric population, but less aggressive if we compare with the adult one [7]. Congolese patients presented an aggressive course.…”
Section: Discussionmentioning
confidence: 95%
“…They were young adults. The literature review from 2001 to 2020 has shown that the incidence is higher in the pediatric population, but less aggressive if we compare with the adult one [7]. Congolese patients presented an aggressive course.…”
Section: Discussionmentioning
confidence: 95%
“…While the incidence of SCIC is higher in children than in adults, adults tend to experience a more aggressive disease course with mortality rate as high as 50%. [5] Diagnosis of SCIC calls for primary biliary disease to be ruled out, which is most commonly done using ultrasound which has a positive predictive value of 95% in diagnosing acute cholecystitis. [7] Since our patient had a history of cholecystectomy, cholecystitis was not in the differential diagnosis, and there was no evidence of biliary obstruction on either abdominal ultrasound or CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…SCIC has a poor prognosis and carries a high mortality (up to 40%) that has been altered by early use of exchange transfusions. 5 This was attempted in our patient after her liver transplant to decrease graft injury associated with sickle cell anemia. In sickle cell patients in whom this fails, liver transplantation is the only option.…”
Section: Discussionmentioning
confidence: 99%